Discourse Analysis of Femicide Reporting in the Mass Media on the Tribun News YouTube Page: Sara Mills' Perspective - Sani, Mutiara; Julianti, Ulfah (Universitas Muria Kudus, 2024)
The aim of this research is to describe the subject-object position and writer-reader position in the discourse of reporting femicide via the Tribun News YouTube page using the Sara Mills model of discourse study analysis. The method in this research uses a qualitative descriptive approach. The data collection technique was carried out using listening techniques, namely listening without being involved, listening, recording and taking notes. The data source used in this research comes from the Tribun News YouTube page for the 2019-2024 period. The results of the analysis show that from the Tribun News video, 9 news stories were found that indicated the issue of femicide which placed the perpetrator as an active subject and the victim as a passive object. News writers act as conveyers of information who often take a neutral position but have a big influence in shaping readers' views. Through word choice and narrative focus, the author can move the reader's emotions to feel sympathy for the victim and hatred for the perpetrator. Readers, on the other hand, are positioned as recipients of information who are expected to respond emotionally to the events reported, especially through the presentation of the often dramatic and horrific details of the crime.